The politics of global tax governance - Schmidtke, Henning (Routledge, 2019)
Why has global tax governance been politicized and how can we explain the varying intensity and content of public debates? This book offers an integrated theory of the politicization of international institutions and a detailed account of how the institutional design and policy output of tax governance by the EU and OECD have developed over time. Offering the first in-depth empirical analysis to compare politicization across international institutions, it blends institutionalist explanations that focus on the growing authority of international institutions, and sociological and political economy approaches that take into account domestic context. Exploring why and how international institutions have become increasingly contested in the 21st century, this book will be of particular interest to the scholars of the transfer of authority from the nation-state to international institutions, and the societal repercussions and political struggles that connect these processes. Researchers in the fields of political science, international relations, sociology, and political communication will also find it useful and insightful
Keywords: Internationale Organisation; Governance; Steuerpolitik; Taxation / International cooperation; Taxation / Political aspects; International finance; International relations; BUSINESS & ECONOMICS / Public Finance; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / Trade & Tariffs; Electronic books